Case Report: Adjunctive hemoadsorption therapy in a patient with Takotsubo cardiomyopathy and hyperinflammation - Castro, Jose O. (Frontiers in Medicine, 2025)
IntroductionTakotsubo cardiomyopathy (TCM) is a transient, stress-related cardiac dysfunction that mimics acute coronary syndrome and is typically seen in postmenopausal women. While emotional and physical stressors are common triggers, inflammatory or infectious stimuli have also been proposed, although the underlying mechanisms remain incompletely understood. In the context of critical illness, systemic inflammation may exacerbate cardiac dysfunction and contribute to multiorgan failure. Hemoadsorption has emerged as a promising adjunctive therapy option aimed at mitigating hyperinflammation by removing circulating cytokines and other inflammatory mediators, and has shown potential benefit in various inflammatory conditions.Case descriptionA 77-year-old woman with hypertension, diabetes, and a permanent pacemaker presented with acute dyspnea and subsequently experienced cardiac arrest. Post-resuscitation, she was found to have anterolateral ST elevations, apicomedial akinesis, and severely reduced LVEF (22%), consistent with Takotsubo cardiomyopathy. Despite appropriate antimicrobial therapy and supportive care, she developed worsening fever, marked hemodynamic instability, hyperlactatemia (14 mmol/L), atrial fibrillation, raising suspicion for a systemic hyperinflammatory response. Hemoadsorption therapy with CytoSorb was initiated in a stand-alone configuration, alongside corticosteroids and targeted temperature management. The patient showed marked improvement in hemodynamics, organ function, and urine output within 48 h, without the need for renal replacement therapy. She was later extubated and discharged home.ConclusionThis case highlights a rare presentation of suspected inflammation-triggered Takotsubo cardiomyopathy complicated by rapid clinical deterioration. The use of CytoSorb hemoadsorption was associated with stabilization of vital parameters and recovery of organ function. Although causality cannot be confirmed, this case supports the early consideration of hemoadsorption as a feasible and potentially beneficial adjunct in select critically ill patients with suspected hyperinflammation. Further research is needed to clarify its role in TCM and related syndromes.